Peningkatan Aktifitas Kolaboratif Dan Hasil Belajar. Siswa Melalui Guided Discovery Learning Berbantuan Puzzel - Awaluddin, Awaluddin; Inganah, Siti; Jamil, Anis Farida; Dintarini, Mayang; Zukhrufurrohmah, Zukhrufurrohmah (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2018)
Nowadays, the government is promoting the Individual Learning Activity Sheet (UKBM) for the student in mathematics learning. UKBM provides opportunities for students to study independently and provides the chance for students to complete assignments (UKBM) differently for each student in one class. The aim of this study was to increase collaborative activity skills and student’s learning outcomes through puzzle-assisted Guided Discovery Learning learning models. This study was a classroom. action research within two cycles consisting of the planning stage, implementation stage, observation stage, and reflection stage. The instruments used were observation sheets and test sheets. The teaching material is UKBM. The results of a guided discovery learning study assisted by puzzles with UKBM teaching materials there is an increase in student’s collaborative abilities and learning outcomes. Keywords: Guided Discovery Learning, Collaborative Ability, Learning Outcomes, Media Puzzle